Elliptic problems on weighted locally finite graphs - Imbesi, Maurizio; Bisci, Giovanni Molica; Repovš, Dušan D. (Topological Methods in Nonlinear Analysis, 2023)
Let G:= (V,E) be a weighted locally finite graph whose finite measure μ has a positive lower bound. Motivated by a wide interest in the current literature, in this paper we study the existence of classical solutions for a class of elliptic equations involving the μ-Laplacian operator on the graph G, whose analytic expression is given by equation* Δ_μ u(x) := 1μ (x) _yx w(x,y) (u(y)-u(x))(for all xV), equation* where w V× V → [0,+∞) is a weight symmetric function and the sum on the right-hand side of the above expression is taken on the neighbours vertices x,yV, that is xy whenever w(x,y) > 0. More precisely, by exploiting direct variational methods, we study problems whose simple prototype has the following form equation*Np000 cases -Δ_μ u(x)=λ f(x,u(x))&for x D^ °, u|_D=0, cases equation* where D is a bounded domain of V such that D^ ° eq and D eq , the nonlinear term f D × → satisfy suitable structure conditions and λ is a positive real parameter. By applying a critical point result coming out from a classical Pucci-Serrin theorem in addition to a local minimum result for differentiable functionals due to Ricceri, we are able to prove the existence of at least two solutions for the treated problems. We emphasize the crucial role played by the famous Ambrosetti-Rabinowitz growth condition along the proof of the main theorem and its consequences. Our results improve the general results obtained by A. Grigor’yan, Y. Lin, and Y. Yang in GLY2.